(NbRATXQ kARAMAZOWY(B: [(NrOMAN(B] s (N~ASTI (BI-III /s (N~ASTX (B9s - (NdOSTOEWSKIJ(B, (NfEDORs ((NlENINGRAD(B:s (NnAUKA(B,s, 1990)
(Nw DEWQTYJ TOM sOBRANIQ SO^INENIJ WO[LI PERWYE TRI ^ASTI ROMANA (B"(NbRATXQ kARAMAZOWY(B".s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NpSIHOLOGI^ESKIJ ROMANs